The efficacy of sodium benzoate and potassium sorbate in inhibiting the growth of food fungi and bacteria - Romli, Nurul Fatin Amilia; Sukor, Rashidah; Rukayadi, Yaya; Mohsin, Aliah Zannierah (Prince of Songkla University, 2022)
Bacterial and fungal resistance to chemical preservatives is a major food safety issue with significant health and economic ramifications. The efficacy of food preservatives in inhibiting the growth of fungi and bacteria is crucial to ensure the safety and quality of food products. This study aimed to determine the efficacy of sodium benzoate and potassium sorbate against food fungi and bacteria. Four spoilage fungi (Aspergillus sp., Trametes sp., Penicillium sp., Cladosporium sp.) were isolated from mango, lemon, and orange. Sodium benzoate and potassium sorbate were tested at 100, 200, 300, and 400 mg/L for antimicrobial properties against the isolated fungi and bacteria (S. enterica, E. coli, K. pneumonia, Proteus sp., S. aureus, B. cereus, and B. subtilis) using pour plate method. Results showed that sodium benzoate was effective against all microorganisms tested, except for B. cereus and Aspergillus sp.: the growth of both microorganisms was inhibited at 400 mg/L. Meanwhile, potassium sorbate was found to be effective against all tested microorganisms at 100 mg/L. In conclusion, both preservatives were proven to be effective against bacteria and fungi found in food. This information is useful as guidance for food manufacturers to apply preservatives targeting microorganisms at effective levels.